Analisis Pemahaman Bacaan Shalat pada Siswa SMA Negeri 2 Payakumbuh - Widya Yolanda; Wirdati Wirdati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Prayer is a means of communication of a servant with Allah SWT. The practice of praying is not only doing it, but also having to understand the meaning of the readings recited in prayer, because the quality of a servant's communication with Allah SWT is strongly influenced by the quality of the communication tool or how to communicate it. This study aims to determine how the students' reading comprehension of prayers at SMA Negeri 2 Payakumbuh. The population of this descriptive quantitative research is the students of class X and XI at SMA Negeri 2 Payakumbuh, totaling 788 students. The sampling technique used the slovin formula, obtained a sample of 88 students. Data collection techniques are through tests. Based on the results of the research obtained through tests, for the reading comprehension of prayers, the students of SMA Negeri 2 Payakumbuh are in the category of lack of understanding. This is evidenced by 49%, almost half of the students are in the category of lack of understanding, 27% of which are very understanding, 15% understand little, and 9% do not understand very little. It is hoped that parents and teachers can optimize prayer learning.